NFM-07. SPRINT: PHASE II STUDY OF THE MEK 1/2 INHIBITOR SELUMETINIB (AZD6244, ARRY-142886) IN CHILDREN WITH NEUROFIBROMATOSIS TYPE 1 (NF1) AND INOPERABLE PLEXIFORM NEUROFIBROMAS (PN). Issue 2 (22nd June 2018) - Gross, Andrea; Wolters, Pamela; Baldwin, Andrea; Dombi, Eva; Fisher, Michael J; Weiss, Brian; Kim, AeRang; Blakeley, Jaishri; Whitcomb, Patricia; Holmblad, Marielle; Maritin, Staci; Roderick, Marie Claire; et al.
Abstract: PN in NF1 cause substantial morbidity. In a phase I trial of selumetinib, 17/24 patients had a partial response (PR). This study evaluates the PR rate of PN to selumetinib and changes in PN-related morbidities. Patients 2-18 years with NF1, inoperable PN and ≥ 1 PN-related morbidity received continuous 28-day cycles of selumetinib (25 mg/m 2 PO BID). Response (volumetric MRI analysis; PR = PN volume decrease ≥20%) and PN-related morbidities were assessed after every 4 cycles. Fifty children (30 male, median age 10.2 years, range 3.5, 17.4) enrolled. Disfigurement (n=44), motor dysfunction (n=33) and pain (n=28) were the most frequent PN-related morbidities. As of November 5, 2017: median cycle number 19.5 (range 0, 29); median change in PN volume -27.7% (range -50.6%, 2.2%). Best response PR (36 patients, 72%), stable disease (12 patients, 24%); 2 (4%) had no re-staging evaluations. Of the 36 PR, 32 were confirmed on ≥ two consecutive restaging studies. Pain intensity and interference scores improved significantly (p <0.01) over one year, as did strength (0-5 scale) and range of motion (degrees) (p < 0.01). Most frequent toxicities: gastrointestinal, asymptomatic creatine kinase increase, acneiform rash and paronychia. Selumetinib dose was reduced in 12 patients, of which 5 were removed from treatment. The response rate from this study (72%) confirms our previously observed rate (71%). Most responses have lasted ≥6 months. Improvements in PN-related pain and motor impairment demonstrate that selumetinib can provide clinical benefit. Data validation and further analyses are ongoing.